2016
DOI: 10.1002/ajcp.12091
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Disaster Recovery Work Influence Mental Health?: Pathways through Physical Health and Household Income

Abstract: Disaster recovery work increases risk for mental health problems, yet the mechanisms underlying this association are unclear. We explored links from recovery work to posttraumatic stress (PTS), major depression (MD) and generalized anxiety disorder (GAD) symptoms through physical health symptoms and household income in the aftermath of the Deepwater Horizon oil spill. As part of the NIEHS GuLF STUDY, participants (N = 10,141) reported on cleanup work activities, spill-related physical health symptoms, and hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The emotional stress related to the spill was also a possible cause of increased physical health risks such as heart attacks (Strelitz et al, 2018). Other analyses suggest that physical health symptoms contribute to cleanup workers' risk for mental health issues (Lowe, 2016). However, fishers who had longer periods of cleanup work and thus potentially higher work-related oil exposure also had higher income, which in turn is associated with lower anxiety and depression (Lowe et al, 2016).…”
Section: Worker Health Findingsmentioning
confidence: 99%
“…The emotional stress related to the spill was also a possible cause of increased physical health risks such as heart attacks (Strelitz et al, 2018). Other analyses suggest that physical health symptoms contribute to cleanup workers' risk for mental health issues (Lowe, 2016). However, fishers who had longer periods of cleanup work and thus potentially higher work-related oil exposure also had higher income, which in turn is associated with lower anxiety and depression (Lowe et al, 2016).…”
Section: Worker Health Findingsmentioning
confidence: 99%
“…However, because this was a cross-sectional survey, there was potential for reverse causality between cleanup participation and anxiety symptoms, both assessed after the oil spill. 27 It is also unknown whether respondents who participated in oil spill cleanup activities were healthier at baseline and had fewer mental health conditions. As the Gulf States Population Survey was a random-digit-dial telephone survey, the associations may introduce bias due to potential effects of recall bias or social desirability bias among the study participants.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…A disaster of such magnitude has detrimental effects on people living in both directly and indirectly affected areas, as this disaster impacted coastal communities as well as members of the response and cleanup efforts who were not exclusively local residents (Aguilera, Mendez, Pasaro, & Laffon, 2010;Laffon, Pasaro, & Valdiglesias, 2016). Research on the health effects of the oil spill identified rises in reports of depression Buttke, Vagi, Schnall, et al, 2012;Fan, Prescott, Zhao, Gotway, & Galea, 2015;Kwok, McGrath, et al, 2017;Lowe et al, 2016;Osofsky, Osofsky, & Hansel, 2011;Rung et al, 2016). Also, increases in anxiety were found among persons residing in places impacted by the oil spill Buttke, Vagi, Schnall, et al, 2012;Gould, Teich, Pemberton, Pierannunzi, & Larson, 2015;Lowe et al, 2016;Osofsky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the health effects of the oil spill identified rises in reports of depression Buttke, Vagi, Schnall, et al, 2012;Fan, Prescott, Zhao, Gotway, & Galea, 2015;Kwok, McGrath, et al, 2017;Lowe et al, 2016;Osofsky, Osofsky, & Hansel, 2011;Rung et al, 2016). Also, increases in anxiety were found among persons residing in places impacted by the oil spill Buttke, Vagi, Schnall, et al, 2012;Gould, Teich, Pemberton, Pierannunzi, & Larson, 2015;Lowe et al, 2016;Osofsky et al, 2011). Other studies examining the effects of the spill reported a greater occurrence of physical distress Buttke, Vagi, Schnall, et al, 2012;Fan et al, 2015;Gam et al, 2018;McGowan et al, 2017;Peres et al, 2016).…”
Section: Introductionmentioning
confidence: 99%